Broadband miniaturized 180° phase shifter based on symmetric coupling structure. Issue 11 (1st July 2022) - Zhang, Zhe; Guan, Meng; An, Kang; Chen, Aixin
Abstract: An electronically reconfigurable wideband 180° phase switch using microstrip–slotline transitions is proposed. Multilayer structure with microstrips on the bottom and top layers, slotline on the middle layer confirm the broadband transmission. Taking advantage of the symmetry of the transition, only two p–i–n diodes are integrated on the top microstrip layer to achieve a 0°/180° phase reconfiguration. Miniaturized design is achieved with a size of 0.26 λg × 0.16 λg . The measured results are in good agreement with the simulated results, which show less than 5° phase deviation and less than 1.5 dB insertion loss across the band 0.68–2.5 GHz.